Seeking the common dreams between the worlds : stories of Chinese immigrant faculty in North American higher education - Wang, Yan (Professor of education); Zhao, Yali (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This is the first book that probes the lived experiences of Chinese immigrant faculty in North American higher education institutions: their struggles, challenges, successes, etc. It explores how their past experiences in China have shaped who they are now, what they do and how they pursue their teaching, research, and service, as well as the reality of their everyday life that inevitably intertwines with their present and past diverse cultural backgrounds and unique experiences.Different from previous books that explore immigrant/minority faculty defined ambiguously and broadly and from the theoretical framework of ethnic relations, this book has a particular focus on mainland Chinese immigrant faculty, which offers a richer and deeper understanding of their cross-culture experiences through autoethnographic research and by multiple lenses. Through authors' vivid portray of the ebbs and flows of their life in the academe, readers will gain an enjoyable and holistic knowledge of the cultural, political, linguistic, scholarly, and personal issues contemporary Chinese immigrant faculty encounter as they cross the border of multiple worlds.All contributors to this book had the experience of being the first-generation Chinese immigrants, and they either are currently teaching or used to teach in North American higher education institutions, who were born, brought up, educated in Mainland China and came to North America for graduate degrees from early 1980s to 2000.